2002
DOI: 10.1086/341195
|View full text |Cite
|
Sign up to set email alerts
|

Statistics, Morphology, and Energetics of Ellerman Bombs

Abstract: We investigate the statistical properties of Ellerman bombs in the dynamic emerging flux region NOAA Active Region 8844, underneath an expanding arch filament system. High-resolution chromospheric H filtergrams (spatial resolution 0>8), as well as photospheric vector magnetograms (spatial resolution 0>5) and Dopplergrams, have been acquired by the balloon-borne Flare Genesis Experiment. H observations reveal the first '' seeing-free '' data set on Ellerman bombs and one of the largest samples of these events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
287
7
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(334 citation statements)
references
References 52 publications
36
287
7
4
Order By: Relevance
“…Therefore, it is expected that QSLs may occur in the low atmosphere and EBs are triggered somewhere along QSLs. EB triggering by magnetic reconnection on QSLs was also favoured by the observational data obtained by Georgoulis et al (2002).…”
Section: Topology Around Ellerman Bombsmentioning
confidence: 54%
See 4 more Smart Citations
“…Therefore, it is expected that QSLs may occur in the low atmosphere and EBs are triggered somewhere along QSLs. EB triggering by magnetic reconnection on QSLs was also favoured by the observational data obtained by Georgoulis et al (2002).…”
Section: Topology Around Ellerman Bombsmentioning
confidence: 54%
“…Kitai (1983) found that a density enhancement (by a factor of 5) and a hot temperature gradient (≈1500 K) may account for the line broadening in EBs. Georgoulis et al (2002) and Pariat et al (2004) also found that the temperature increases by ≈2000 K at the sites of EBs. In our simulations, the density enhancement is close to the value reported by Kitai (1983).…”
Section: Comparison With Observations: Ellerman Bombsmentioning
confidence: 85%
See 3 more Smart Citations